Acacia gum polysaccharide based hydrogel wound dressings: Synthesis, characterization, drug delivery and biomedical properties. (1st June 2017) - Singh, Baljit; Sharma, Sushma; Dhiman, Abhishek
Graphical abstract: Highlights: Hydrogel dressings are porous network structure. Drug release followed non Fickian mechanism. Drug release profile best fitted in the Higuchi model. Wound dressings are antioxidant, non-haemolytic and mucoadhesive in nature. Histological study showed accelerated wound healing. Abstract: Keeping in view the importance of polysaccharide gums for wound care, in the present article, an attempt has been made to explore antioxidant nature of gum acacia in designing hydrogel wound dressing to improve its wound healing potential. These polymers were prepared by using acacia gum-polyvinylpyrollidone/carbopol and were characterized by 13 C NMR, FTIR, SEM, AFM, cryo-SEM, XRD, TGA, DSC and elemental analysis techniques. Some important biomaterial properties of wound dressings such as wound fluid absorption, haemo-compatibility, bioactive assessment, gaseous/water/microbial permeability, mechanical properties, bio-adhesion, drug release, and histology of wound healing were also determined. Hydrogel wound dressings were found non-haemolytic, antioxidant and mucoadhesive in nature. Release of drug occurred through non-Fickian diffusion mechanism and release profile best fitted in Higuchi model.